Minimizing blood loss in laparoscopic myomectomy with temporary occlusion of the hypogastric artery - Balulescu, Ligia; Nistor, Samuel; Lungeanu, Diana; Brasoveanu, Simona; Pirtea, Marilena; Secosan, Cristina; Grigoras, Dorin; Caprariu, Radu; Pasquini, Andrea; Pirtea, Laurentiu (Frontiers in Medicine, 2023)
Introduction Uterine leiomyomas are common benign pelvic tumors. Currently, laparoscopic myomectomy (LM) is the preferred treatment option for women in the fertile age group with symptomatic myomas. The authors hypothesize that combining LM with a bilateral temporary occlusion of the hypogastric artery (TOHA) using vascular clips minimizes uterine blood flow during surgery and can significantly reduce surgery-associated blood loss. Materials and methods This single-center, prospective randomized study was conducted at the Department of Obstetrics and Gynecology, Municipal Emergency Clinical Hospital Timisoara, Romania. Patients aged between 18 and 49 who preferred laparoscopic myomectomy and wished to preserve fertility were included, provided they had intramural uterine leiomyomas larger than 4 cm in diameter that deformed the uterine cavity. The study analyzed data from 60 laparoscopic myomectomies performed by a single surgeon between January 2018 and December 2020. Patients were randomly assigned to either: “LM + TOHA” group (29 patients), and “LM” group (31 patients). The study’s main objective was to evaluate the impact of TOHA on perioperative blood loss, expressed as mean differences in Hb (delta Hb). Results Delta Hb was statistically lower in the “LM + TOHA” group compared to “LM” group, with mean ± standard (min–max): 1.68 ± 0.67 (0.39–3.99) vs. 2.63 ± 1.06 (0.83–4.92) g/dL, respectively (p < 0.001). There was a statistically significant higher need for postoperative iron perfusion in the “LM” group, specifically 0 vs. 12 patients (p < 0.001), and lower postoperative anemia in “LM + TOHA” group (p < 0.001). Necessary artery clipping time was 10.62 ± 2.47 (7–15) minutes, with no significant impact on overall operative time: 110.2 ± 13.65 vs. 106.3 ± 16.48 (p = 0.21). There was no difference in the length of hospitalization or 12-month post-intervention fertility. Discussion Performing bilateral TOHA prior to laparoscopic myomectomy has proven to be a valuable technique in reducing surgery-associated blood loss, while minimizing complications during surgery, with no significant increase in the overall operative time. Clinical trial registration ISRCTN registry, (www.isrctn.com), identifier ISRCTN66897343.